2023
DOI: 10.3390/pharmaceutics15010303
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Optimisation of Smart Linker Chemistry for Targeted Colonic Delivery—In Vitro Evaluation

Abstract: Drug targeting is necessary to deliver drugs to a specific site of action at a rate dictated by therapeutic requirements. The pharmacological action of a drug can thereby be optimised while minimising adverse effects. Numerous colonic drug delivery systems have been developed to avoid such undesirable side effects; however, these systems lack site specificity, leaving room for further improvement. The objective of the present study was to explore the potential of amino-alkoxycarbonyloxymethyl (amino-AOCOM) eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In contrast, prodrug 2 cyclises more slowly to form a sixmembered ring, releasing > 55% of the payload over 5 h at the same pH [24]. Increasing the methylene spacer length to four carbons-such as in prodrug 4, which we reported recently [25]-hinders the cyclisation further and slows down drug release accordingly (in this case, achieving 92% release of mesalamine over 6 d at pH 6.5). Therefore, in the case of RAL (where long-acting prodrugs are required), we tried extending the methylene spacer to five or six carbons (corresponding to eight-and ninemembered ring cyclisations) in our initial model probes, to obtain the very slow-release Therefore, in the case of RAL (where long-acting prodrugs are required), we tried extending the methylene spacer to five or six carbons (corresponding to eight-and ninemembered ring cyclisations) in our initial model probes, to obtain the very slow-release kinetics suitable for development of a long-acting SC injection.…”
Section: Proposed Release Mechanismmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, prodrug 2 cyclises more slowly to form a sixmembered ring, releasing > 55% of the payload over 5 h at the same pH [24]. Increasing the methylene spacer length to four carbons-such as in prodrug 4, which we reported recently [25]-hinders the cyclisation further and slows down drug release accordingly (in this case, achieving 92% release of mesalamine over 6 d at pH 6.5). Therefore, in the case of RAL (where long-acting prodrugs are required), we tried extending the methylene spacer to five or six carbons (corresponding to eight-and ninemembered ring cyclisations) in our initial model probes, to obtain the very slow-release Therefore, in the case of RAL (where long-acting prodrugs are required), we tried extending the methylene spacer to five or six carbons (corresponding to eight-and ninemembered ring cyclisations) in our initial model probes, to obtain the very slow-release kinetics suitable for development of a long-acting SC injection.…”
Section: Proposed Release Mechanismmentioning
confidence: 68%
“…In contrast, prodrug 2 cyclises more slowly to form a six-membered ring, releasing >55% of the payload over 5 h at the same pH [ 24 ]. Increasing the methylene spacer length to four carbons—such as in prodrug 4 , which we reported recently [ 25 ]—hinders the cyclisation further and slows down drug release accordingly (in this case, achieving 92% release of mesalamine over 6 d at pH 6.5).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To evaluate the pH‐responsive behavior of this system, mesalamine was loaded in the polymeric nanocarriers. It was reported that this novel polymeric system released more than 90% of the drug at colonic pH, thus protecting a significant amount of the drug from the acidic environment of the stomach 167 …”
Section: Applications Of Polyelectrolytes In Drug Deliverymentioning
confidence: 99%
“…It was reported that this novel polymeric system released more than 90% of the drug at colonic pH, thus protecting a significant amount of the drug from the acidic environment of the stomach. 167…”
Section: Colon Targeted Drug Deliverymentioning
confidence: 99%